EFFECTIVENESS OF LAW ENFORCEMENT AGAINST HUMAN TRAFFICKING CRIMES IN THE EAST JAVA REGIONAL POLICE AREA - Putu Laraswati Padma Dewi; M.A Razak (DE RECHT (Journal of Police and Law Enforcement), 2025)
Human trafficking (tindak pidana perdagangan orang/TPPO) constitutes a grave transnational crime that systematically violates human dignity through coercion, deception, and exploitation. This study examines the effectiveness of law enforcement against TPPO within the jurisdiction of the East Java Regional Police (Polda Jawa Timur), with reference to Law Number 21 of 2007 on the Eradication of Human Trafficking Crimes. A normative juridical method was employed, drawing on primary legal sources including applicable legislation and judicial decisions, secondary sources comprising academic literature and prior research findings, and tertiary sources for conceptual clarification. Analysis was conducted through a descriptive-analytical approach using deductive reasoning. The findings indicate that enforcement in this jurisdiction has progressed notably in its prosecutorial dimension, as demonstrated by increased case disclosure rates, the operationalization of an integrated multi-agency task force, and consistent suspect referral to judicial proceedings. However, enforcement effectiveness remains structurally incomplete, with victim protection, psychosocial rehabilitation, and reintegration support lagging behind punitive achievements. Principal obstacles include evidentiary challenges arising from victim trauma, insufficient officer specialization, fragmented inter-agency coordination, the absence of a unified national case management system, and a growing asymmetry between perpetrators' digital recruitment capabilities and the investigative capacity of regional units. This study recommends sustained investment in officer training, inter-agency data integration, victim service infrastructure, and international enforcement cooperation as priority measures to advance comprehensive and rights-based TPPO enforcement.